Inappropriate Questions in the Confessional: Canon 979 - Daly, Brendan (Roman replies and CLSA advisory opinions ; 2010, 2010)
When a confessor is repeatedly accused of asking inappropriate questions regarding sexual matters what options does the diocesan bishop have?